2015
DOI: 10.1073/pnas.1424386112
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plant compounds that disrupt the insect juvenile hormone receptor complex

Abstract: Insects impact human health through vector-borne diseases and cause major economic losses by damaging crops and stored agricultural products. Insect-specific growth regulators represent attractive control agents because of their safety to the environment and humans. We identified plant compounds that serve as juvenile hormone antagonists (PJHANs). Using the yeast twohybrid system transformed with the mosquito JH receptor as a reporter system, we demonstrate that PJHANs affect the JH receptor, methoprene-tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 20 publications
1
62
0
1
Order By: Relevance
“…The two peaks within the highly differentiated X-linked locus include genes controlling juvenile hormone and ecdysteroid signaling whose perturbation is a common target of plant defensive toxins (48,49). Mutations in genes affecting the ecdysteroid metabolism pathway have enhanced D. sechellia adaptation on toxic noni (20) and helped make Drosophila pachea an obligatory specialist on a toxic cactus (9).…”
Section: Discussionmentioning
confidence: 99%
“…The two peaks within the highly differentiated X-linked locus include genes controlling juvenile hormone and ecdysteroid signaling whose perturbation is a common target of plant defensive toxins (48,49). Mutations in genes affecting the ecdysteroid metabolism pathway have enhanced D. sechellia adaptation on toxic noni (20) and helped make Drosophila pachea an obligatory specialist on a toxic cactus (9).…”
Section: Discussionmentioning
confidence: 99%
“…It is the balance in levels of these two hormones that define the outcome of each developmental transition [59]. Ligand-binding to the insect juvenile receptor complex disrupt insect endocrine signaling and regulation causing abnormal development and lethality [21]. The accumulation of these plant compounds above threshold levels disrupt the insects’ developmental progression culminating into premature death or failure to emerge as a normal adult [60].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being a rich source of bioactive pharmacophores, plants produce allelochemicals with great potential of controlling crop pests and disease-transmitting vectors [21, 22]. Among these are essential oils documented to repel nuisance human biting mosquitoes in addition to inducing toxicity to developing juveniles [2325].…”
Section: Introductionmentioning
confidence: 99%
“…The yeast two‐hybrid binding test using quantitative β ‐galactosidase assay was carried out using Y‐187 yeast cells transformed with A. aegypti Met‐FISC as previously described (Lee et al . ). The transformed Y187 cells were incubated at 30°C in DDO (SD ‐Leu/−Trp) media until OD 600 values reached 0.3–0.4.…”
Section: Methodsmentioning
confidence: 97%
“…Recently, it has been reported that one of the chalcone derivatives, kanakugiol, acts as a juvenile hormone antagonist (JHAN) by disrupting the juvenile hormone receptor complex (Lee et al . ). JHANs could be effective for control of insect pests because they fatally affect the JH‐regulated phyisiological processes such as molting, metamorphosis, reproduction, polyphenism, caste differentiation, and various physiological functions in insects (Riddiford ; Nijhout ; Raikhel et al .…”
Section: Introductionmentioning
confidence: 99%